Uses of Telehealth in Elderly Patients during COVID-19 Pandemic: An Integrative Review - Narvaez, Roison Andro; Ferrer, Marilane; Peco, Ralph Antonio; Sangilan, Neil Bryant; Topacio, Ronalyn (International Journal of Computing Sciences Research; Vol 6 (2022): Vol 6, 2022)
Purpose – The coronavirus disease-19 (COVID-19) epidemic is a significant public health concern on a global scale. Telehealth could be used to combat the COVID-19 outbreak. During the COVID19 epidemic, the goal of this integrative review was to examine the applications, functions, and consequences of telehealth services in preventing disease, diagnosis, medication, and mitigation, especially in long-term care settings or in elderly patients. Method – The five web databases searched were PubMed, ResearchGate, Google Scholar, Web of Science, and Science Direct. The inclusion criteria were studies that documented the explicit use of telehealth services in all elements of health care for older adults during the COVID-19 outbreak, were written in English, and were published in e-journals. The Critical Appraisal Skills Program (CASP) checklist was used to determine the quality (McMaster University Hamilton, 2011). The findings were tabularized. Results – Out of 69 search results, eight studies met the criteria for inclusion. Telehealth is currently an effective method for healthcare practitioners, front liners, COVID19 patients, especially the elderly, who are self-isolating to reduce the risk of COVID-19 transmission. This technique can significantly eliminate direct physical contact, maintain community care, and eventually minimize COVID-19 outbreak morbidity and mortality. Conclusion – Telehealth simplifies the process of providing health care to the elderly. As a result, telehealth should be a vital component of providing care while also safeguarding older patients and health care providers throughout the COVID-19 outbreak. Implications – Telehealth was highly used in the COVID19 pandemic era. The specific uses and functions of telehealth during the pandemic, specifically to the elderly, is significant in the aspect of patient care.